Are Lifestyle Therapies Effective for NAFLD Treatment?. (October 2019) - El-Agroudy, Nermeen N.; Kurzbach, Anica; Rodionov, Roman N.; O'Sullivan, John; Roden, Michael; Birkenfeld, Andreas L.; Pesta, Dominik H.
Abstract : Nonalcoholic fatty liver disease (NAFLD) is becoming the most common liver disorder worldwide. Specifically, nonalcoholic steatohepatitis (NASH) and fibrosis pose an enormous burden for patients and health-care systems. In the absence of approved pharmacological therapies, effective lifestyle interventions for NAFLD, such as dietary strategies and exercise training, are currently the therapeutic strategies of choice. This review covers the influence of macronutrient quality and quantity (i.e., low-carbohydrate and high-protein diets), for successful reduction of intrahepatocellular lipids (IHL). Moreover, we discuss the effectiveness of different modalities of physical exercising with and without weight loss. These lifestyle modifications not only provide strategies to reduce IHL but may also hold a still underestimated potential to induce improvement and/or even remission of NAFLD. Highlights: Due to its high prevalence, nonalcoholic fatty liver disease (NAFLD) is becoming an increasingly important health issue. In the absence of an established pharmacological therapy, lifestyle therapies, including dietary modifications and physical activity, are of increasing clinical significance. Although weight loss can improve IHL, distribution of macro- and micronutrients, the role of total calories, type of diet, and physical activity is less clear. Some evidence suggests consumption of a Mediterranean diet, high fiber and protein intake, as well as physical activity, regardless of modality or intensity, have beneficial effects on intrahepatic lipids. Recent advances also indicate that meal timing, such as shifting a higher number of daily calorie intake to the morning, can benefit NAFLD.